Practical Rails Projects - Alameda, Eldon (Apress : Imprint: Apress, 2007)
The best way to learn Rails is by creating a variety of applications with it. You already know the basics of Rails, and you're familiar with the exciting features and benefits associated with using this Ruby-based framework. You're now at the point where you need to gain firsthand experience with Rails by thoroughly exploring the features and building several different types of web applications. Eldon Alameda takes a focused approach to guiding you through the creation of multiple real-world examples that are designed to get your hands dirty with the core features of Rails, while providing you with the valuable experience of creating real Rails applications. Projects you'll work on include creating a simple blog with an external API, constructing a workout tracker with a RESTful interface and graphs, and converting an existing PHP site to Rails while adding an advanced JavaScript interface. As an added bonus, the final project makes use of the edge version of Rails as you build an application that utilizes Active Resource, which provides an opportunity to explore the various changes and features that will be included with Rails 2.0. Each project is designed to provide you with the necessary information and tools to give you a running start at solving that problem yourself, and each project includes a number of additional ideas and exercises for ways that you can extend each application to fit your own needs.